1979
DOI: 10.1126/science.760198
|View full text |Cite
|
Sign up to set email alerts
|

Common Origin of Pigment Cells

Abstract: The fundamentally diverse vertebrate pigment cells, melanophores, xanthophores, and iridophores, contain pigmentary organelles known, respectively, as melanosomes, pterinosomes, and reflecting platelets. Their pigments are mealanins pteridines, and purines. Mosaic pigment cells containing more than one type of organelle have been observed and mosaic organelles containing more than one type of pigment have been discovered. It is proposed that the various pigment cells are derived from a stem cell that contains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
163
1
5

Year Published

1980
1980
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(177 citation statements)
references
References 24 publications
8
163
1
5
Order By: Relevance
“…Each platelet is composed primarily of guanine but may also contain other purines such as hypoxanthine, adenine, and uric acid (Fujii, 1993;Le Douarin and Kalcheim, 1999). They usually appear as stacks of empty space in the cytoplasm due to loss of their contents during tissue prep- aration, sectioning (Taylor, 1969;Bagnara et al, 1979), and the damage by electron during TEM observation (Matsumoto, 2001). In our study, iridophore platelets mainly were found as stacks of empty space, although we did sometimes observe iridophores containing platelets surrounded by unit membrane, which may represent more intact condition (Fig.…”
Section: Iridophoresmentioning
confidence: 99%
“…Each platelet is composed primarily of guanine but may also contain other purines such as hypoxanthine, adenine, and uric acid (Fujii, 1993;Le Douarin and Kalcheim, 1999). They usually appear as stacks of empty space in the cytoplasm due to loss of their contents during tissue prep- aration, sectioning (Taylor, 1969;Bagnara et al, 1979), and the damage by electron during TEM observation (Matsumoto, 2001). In our study, iridophore platelets mainly were found as stacks of empty space, although we did sometimes observe iridophores containing platelets surrounded by unit membrane, which may represent more intact condition (Fig.…”
Section: Iridophoresmentioning
confidence: 99%
“…During the development of vertebrates, multipotent neural crest cells give rise to peripheral neuronal cells as well as to pigment cells (27;reviewed in Ref. 28).…”
mentioning
confidence: 99%
“…In the sword tail fish Xiphophorus helleri, as in most vertebrates (Le Lievre, 1978;Johnston et ah, 1979;Bagnara et aL, 1979 andSadaghiani &Thiebaud, 1987), the neural crest cells probably form the presumptive connective tissues adjacent to the eye including the endothetiai and stromal fibroblasts of the cornea. Also, they contribute to the formation of the sclera, pigmented layer of the retina and the iris melanophores.…”
Section: Discussionmentioning
confidence: 99%